Kinematic factors related to forward and vertical release velocity in male javelin throwers - Makino, M.; Tauchi, K. (International Journal of Sport & Health Science, 2022)
The purpose of this study was to determine the kinematic factors related to the forward and vertical release velocities in male javelin throwers. The movements of 115 male javelin throwers who participated in real competitions were videotaped by two cameras, and the coordinate values were obtained using the three-dimensional motion analysis technique. The time-series changes of the kinematic data were calculated, and the relationship with the release velocity of the javelin in the forward and vertical directions was confirmed by calculating the partial correlation coefficient. The forward velocity of the center of gravity of whole body from the right foot contact to left foot contact was commonly higher for throwers with higher forward and vertical release velocities. The angle of trunk backward lean at the left foot contact was smaller (more upright) for throwers with higher forward release velocity and larger for throwers with higher vertical release velocity. At the release, throwers with higher forward release velocity had a higher angular velocity of the right shoulder abduction and horizontal adduction, and throwers with higher vertical release velocity had a higher angular velocity of the trunk forward lean and the right shoulder horizonal adduction. These results indicates that the movements related to the forward and vertical release velocities in the javelin throw are greatly different.